ANALISIS PENGARUH KEPADATAN PERMUKIMAN TERHADAP PELAYANAN INFRASTRUKTUR DI KOTA BANDA ACEH - Fajar Mustika; Muhammad Isya; Ashfa Achmad (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2018)
Service infrastructure related to population density and space usage. This is due to the increasingly crowded population can affect the decrease in public spending per capita, so the quality of public services declined. The purpose of this study was to analyze the effect of settlement density on infrastructures service in Banda Aceh City. The statistical method used is descriptive analysis and Structural Equation Modeling (SEM) analysis through AMOS software. This research was conducted for three weeks by distributing questionnaires to 100 respondents who are head of household domiciled in Banda Aceh City. Based on the result of research, it is found that the density of settlement has negative effect to infrastructure service. This is indicated by the coefficient value of -0,180. The more dense a settlement the infrastructure service in the settlement is less good. The density of settlements negatively affected the use of space with a coefficient value of -0,160. The higher the density of the settlements, the use of space is less good. Spatial use has positive and significant effect on infrastructure service, with coefficient value of 0,471. The better the use of space in a settlement will be better also infrastructure services in the settlement. Improving the quality of infrastructure services due to the use of space is very significant.